Prevalence of disability using rapid assessment of disability toolkit among adult residents of rural Delhi, India - Chauhan, Nitesh; Kaur, Gagan Deep; Khan, Samreen (International Journal Of Community Medicine And Public Health, 2020)
Background: India is committed to ensure development inclusive of persons with disability. Recently a sensitive and specific Rapid Assessment of Disability toolkit has been developed to assess the disability prevalence by United Nations Convention on Disability. Studies using this toolkit in India are inadequate leading to paucity of data regarding disability. The present study was conducted to assess the prevalence of disability among adults of a rural area of Delhi. Methods: A community-based, cross-sectional study, carried out among adults of Fatehpur Beri village, Delhi. A total of 660 participants were assessed using the rapid assessment of disability toolkit. Descriptive statistics were used to calculate the prevalence, Chi-square and Fischer’s exact test was used for bivariate analysis. Results: The prevalence of disability was found to be 8.6% and was similar among both genders. A higher proportion of persons with disability belonged to lower socioeconomic class, were likely to be unmarried, widow/widower, separated/divorced also either illiterate or had studied till primary school only and more often unemployed as compared those without disability. Conclusions: Persons with disability had a significantly lower educational, occupational, socioeconomic attainment. Large scale studies are needed to provide data for planning inclusive development.